Optimasi Tween 80 dan Etanol pada Sediaan Gel Dispersi Padat Ibuprofen Secara Simplex Lattice Design - Jonathan Suneidesis Alpons, Gabriel; Aisiyah, Siti; Harmastuti, Nuraini (Jurnal Farmasi (Journal of Pharmacy), 2021)
Ibuprofen is a part of Non Steroid Anti-Inflamatory Drug (NSAID) that used as treatment of pain or inflammatory. Solid dispersion method may improve the solubility of ibuprofen. Ibuprofen was made into a gel product to overcome the side effect. Addition of an enhancer in a gel may increase the penetration of an active substance. The purpose of this study is to understand the effect of tween 80 and ethanol as an enhancer to penetration and drug release of ibuprofen in gel, the effect to physical quality of gel, and to obtain the optimum formula of the combination of enhancer. This study used simplex lattice design with two factor which is tween 80 and ethanol in gel product formula 1; formula 2; and formula 3 in sequence 100%:0%; 50%:50%; 0%:100%. Solid dispersion of ibuprofen-PEG 6000 was made with melting method and tested with FT-IR before made into gel product. Penetration test is done by using Franz diffusion cell with selofan membrane and the determination of the optimum formula obtained based on counterplot from optimization with design expert 10.0.01 trial version with the parameters of the critical level is viscosity and penetration substanced. The results showed the combination of tween 80 and ethanol could affect viscosity and penetration of active substance, tween 80 had a greater effect than ethanol. The proportion of tween 80 4.681% and ethanol 16.319% produces the optimum formula with the most optimum viscosity, adhesion, and drug penetration